The Effects Of Different Annealing Temperature And Number Of Deposition Layers On The Crystallographic Properties Sodium Niobate (KNN) Thin Films Synthesized By Sol-Gel Spin Coating Technique - Abd Rashid, Mohd Warikh; Mat Harttar @ Mohd Hatta, Maziati Akmal; Azmi, Nurul Azuwa; Azlan, Umar Al-Amani (Penerbit Universiti Teknikal Malaysia Melaka, 2017)
In this paper, the effects of different annealing temperature and number of deposition layers on the crystallographic properties of potassium sodium niobate (KNN) thin films were investigated. X-ray diffraction (XRD) analysis was carried out to determine the crystallographic orientation and phase formation of thin films deposited at different annealing temperatures (600°C, 650°C and 700°C) and various number of deposition layers (1, 2, 3, 4 and 4 layers). The XRD patterns and texture coefficient of the synthesized films confirmed that a highly oriented orthorhombic perovskite structure was obtained at 650°C, while at higher temperature a spurious phase of K4Nb6O17 was evolved. The effective number of deposition layers was found to be five due to the formation of interconnected cracks at sixth deposited layers. The XPPA analysis showed that the unit cell volume of the films was increased gradually from 110.83 cm3 at one layer to 124.31 cm3 at fifth deposited layers. Nevertheless, the lattice strain effect was small and negligible at high layer deposition due to the increased distance of the lattice with the film/substrate interface.